AB1178 AN AUDIT OF ORIGINATOR ADALIMUMAB TO BIOSIMILAR SWITCH IN TWO HOSPITALS. (2nd June 2020) - Mazumder, R.; Loke, M.; Mukhtyar, C.; Gaffney, K.; Balogh, E.; Sekaran, E.; Sultana, M.; Odonkor, M.; Miles, K.
Abstract : Background: Biological drugs have revolutionized the treatment of immune-mediated inflammatory diseases (IMIDs). Current guidelines reserve these drugs for patients with severe refractory disease. Biologic drugs are expensive, but as they reach patent expiry, the introduction of lower-cost biosimilars reduces their impact on health care budgets. It is estimated that NHS England could save £300 million by 2021 following the recent launch of adalimumab biosimilars [1]. As part of this process, there has been a mandatory switch of originator adalimumab to biosimilar adalimumab throughout the U.K. Objectives: To evaluate the impact of the switch to biosimilar adalimumab in individuals with inflammatory arthritis at two NHS trusts in the East of England and calculate the proportion and reasons for switch back to originator adalimumab or a second biosimilar at 12 weeks. Methods: Both hospitals ran dedicated 'switch' clinics. All patient records were reviewed retrospectively. Results: 855 patients with different IMID switched from originator to biosimilar over 13 months. At 12 weeks, 730 patients (85%) maintained the switch, 71 patients (8.7%) switched back to the originator, and 54 patients (6.3%) switched to other biosimilars of the same drug. Conclusion: Switching to a biosimilar was successful in the vast majority of patients and is associated with significant saving. The list prices for originator Adalimumab is £9, 155/person/year and £8, 238/person/year for biosimilar Adalimumab respectively [2]. By switching we will save approximately £719, 402 per annum (9.2% cost reduction). References: [1]NHS England. NHS set to save record £300 million on the NHS's highest drug spend 2018 [cited 2018 November 30]. https://www.england.nhs.uk/2018/11/nhs-set-to-save-record-300-million-on-the-nhss-highest-drug-spend/ [2]https://bnf.nice.org.uk/medicinal-forms/adalimumab.html Disclosure of Interests: Rifat Mazumder: None declared, Marianne Loke: None declared, Chetan Mukhtyar: None declared, Karl Gaffney Grant/research support from: AbbVie, Celgene, MSD, Novartis, Pfizer, and UCB Pharma, Consultant of: AbbVie, Celgene, MSD, Novartis, Pfizer, and UCB Pharma, Speakers bureau: AbbVie, Celgene, MSD, Novartis, Pfizer, and UCB Pharma, Emese Balogh: None declared, Emerald Sekaran: None declared, Mushfika Sultana: None declared, Mabel Odonkor: None declared, Karen Miles: None declared